Polymorphisms and interspecies differences of the activating and inhibitory Fc?RII of Macaca nemestrina influence the binding of human IgG subclasses - Trist, H.; Tan, P.; Wines, B.; Ramsland, Paul; Orlowski, E.; Stubbs, J.; Gardiner, E.; Pietersz, G.; Kent, S.; Stratov, I.; Burton, D.; Hogarth, P. (2014)
Little is known of the impact of Fc receptor (FcR) polymorphism in macaques on the binding of human (hu)IgG, and nothing is known of this interaction in the pig-tailed macaque (Macaca nemestrina), which is used in preclinical evaluation of vaccines and therapeutic Abs. We defined the sequence and huIgG binding characteristics of the M. nemestrina activating Fc?RIIa (mnFc?RIIa) and inhibitory Fc?RIIb (mnFc?RIIb) and predicted their structures using the huIgGFc/huFc?RIIa crystal structure. Large differences were observed in the binding of huIgG by mnFc?RIIa and mnFc?RIIb compared with their human FcR counterparts. MnFc?RIIa has markedly impaired binding of huIgG1 and huIgG2 immune complexes compared with huFc?RIIa (His131). In contrast, mnFc?RIIb has enhanced binding of huIgG1 and broader specificity, as, unlike huFc?RIIb, it avidly binds IgG2. Mutagenesis and molecular modeling of mnFc?RIIa showed that Pro159 and Tyr160 impair the critical FG loop interaction with huIgG. The enhanced binding of huIgG1 and huIgG2 by mnFc?RIIb was shown to be dependent on His131 and Met132. Significantly, both His131 and Met132 are conserved across Fc?RIIb of rhesus and cynomolgus macaques. We identified functionally significant polymorphism of mnFc?RIIa wherein proline at position 131, also an important polymorphic site in huFc?RIIa, almost abolished binding of huIgG2 and huIgG1 and reduced binding of huIgG3 compared with mnFc?RIIa His131. These marked interspecies differences in IgG binding between human and macaque FcRs and polymorphisms within species have implications for preclinical evaluation of Abs and vaccines in macaques. Copyright © 2014 by The American Association of Immunologists, Inc.